US sanctions against South Africa : a historical analysis of the Sanctions Campaign and its political implications ,1946-1993 - De Villiers, Lourens Erasmus Smit (Stellenbosch : Stellenbosch University, 2012)
Dissertation (D. Phil.) -- University of Stellenbosch, 1994.